Infraslow Closed-Loop Brain Training for Anxiety and Depression (ISAD): A pilot randomised, sham-controlled trial in adult females with internalizing disorders. - Perez, Tyson M.; Adhia, Divya B.; Glue, Paul; Zeng, Jiaxu; Dillingham, Peter; Navid, Muhammad S.; Niazi, Imran K.; Young, Calvin K.; Smith, Mark; De Ridder, Dirk (Cognitive, Affective & Behavioral Neuroscience, 2025)
Introduction: The core resting-state networks (RSNs) have been shown to be dysfunctional in individuals with internalizing disorders (IDs; e.g., anxiety, depression). Source-localised, closed-loop brain training of infraslow (≤ 0.1 Hz) EEG signals may have the potential to reduce symptoms associated with IDs and restore normal core RSN function. Methods: We conducted a pilot randomized, double-blind, sham-controlled, parallel-group (3-arm) trial of infraslow neurofeedback (ISF-NFB) in adult females (n = 60) with IDs. Primary endpoints, which included the Hospital Anxiety and Depression Scale (HADS) and resting-state EEG activity and connectivity, were measured at baseline and post 6 sessions. Results: This study found credible evidence of strong nonspecific effects as evidenced by clinically important HADS score improvements (i.e., reductions) across groups. An absence of HADS score change differences between the sham and active groups indicated a lack of specific effects. Although there were credible slow (0.2–1.5 Hz) and delta (2–3.5 Hz) band activity reductions in the 1-region ISF-NFB group relative to sham within the targeted region of interest (i.e., posterior cingulate), differences in activity and connectivity modulation in the targeted frequency band of interest (i.e., ISFs = 0.01–0.1 Hz) were lacking between sham and active groups. Credible positive associations between changes in HADS depression scores and anterior cingulate cortex slow and delta activity also were found. Conclusions: Short-term sham and genuine ISF-NFB resulted in rapid, clinically important improvements that were nonspecific in nature and possibly driven by placebo-related mechanisms. Future ISF-NFB trials should consider implementing design modifications that may better induce differential modulation of ISFs between sham and treatment groups, thereby enhancing the potential for specific clinical effects in ID populations. Trial Registration: The trial was prospectively registered with the Australia New Zealand Clinical Trials Registry (ANZCTR; Trial ID: ACTRN12619001428156).